2015
DOI: 10.1007/s00253-015-6809-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Escherichia coli for production of biodiesel from fatty alcohols and acetyl-CoA

Abstract: Microbial production of biodiesel from renewable feedstock has attracted intensive attention. Biodiesel is known to be produced from short-chain alcohols and fatty acyl-CoAs through the expression of wax ester synthase/fatty acyl-CoA: diacylglycerol acyltransferase that catalyzes the esterification of short-chain alcohols and fatty acyl-CoAs. Here, we engineered Escherichia coli to produce various fatty alcohol acetate esters, which depend on the expression of Saccharomyces cerevisiae alcohol acetyltransferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 54 publications
0
22
0
Order By: Relevance
“…2, 5), suggesting that the alcohol acetyltransferase encoded by ATF1 is the only endogenous enzyme capable of acetylating longer-chain alcohols to any extent. Previous work has shown that ATF1 is capable of acetylating saturated alcohols up to C14 and C16 [24]. Here, by providing exogenous alcohols not typically produced by yeast, we demonstrate that overexpressed ATF1 can acetylate an even wider range of molecules, including fatty alcohols containing up to 18 carbons, with high efficiency.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…2, 5), suggesting that the alcohol acetyltransferase encoded by ATF1 is the only endogenous enzyme capable of acetylating longer-chain alcohols to any extent. Previous work has shown that ATF1 is capable of acetylating saturated alcohols up to C14 and C16 [24]. Here, by providing exogenous alcohols not typically produced by yeast, we demonstrate that overexpressed ATF1 can acetylate an even wider range of molecules, including fatty alcohols containing up to 18 carbons, with high efficiency.…”
Section: Discussionmentioning
confidence: 57%
“…Deletion or overexpression of these genes confirmed their roles in the formation of a broad range of short-chain acetates from propyl acetate up to octyl acetate [22]. It has recently been shown that ATF1 can also acetylate saturated fatty alcohols with a chain length of 14C and 16C when expressed in Escherichia coli [23, 24]. Here, we use both in vivo and in vitro assays to compare the efficiency of the acetyltransferases for acetylation of various fatty alcohols.…”
Section: Introductionmentioning
confidence: 98%
“…Overnight cultures inoculated from single colonies were used to inoculate shake flasks containing M9 medium with 20 g/L glucose as previously described by Guo et al (2015), and shaken at 30 °C as above. The cells were induced at OD600 0.6–0.8 with 0.1 mM IPTG.…”
Section: Methodsmentioning
confidence: 99%
“…Cell cultures were harvested and prepared for wax esters using a previously published method (Guo et al 2015). GC/MS analysis was performed with a DB-5 capillary column.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, one alternative that has stood out is the use of biofuels, such as charcoal, alcohol, biogas and biodiesel. 1,2 Biodiesel is a renewable fuel produced either from vegetable sources (soybean, castor oil, palm oil, sunflower, among others) or from ethanol (from sugarcane) or methanol (which can be obtained from wood biomass). 3 It is, therefore, a biodegradable, sustainable and environmentally friendly fuel.…”
Section: Introductionmentioning
confidence: 99%